Comparison of cavitation intensity in water and in molten aluminium using a high-temperature cavitometer. (November 2015) - Tzanakis, I; Lebon, G S B; Eskin, D G; Pericleous, K
Abstract: The application of ultrasound to industrial casting processes has attracted research interest during the last 50 years. However, the transfer and scale-up of this advanced and promising technology to the industry have been hindered by difficulties in treating large volumes of liquid metal due to the lack of understanding of certain fundamentals. In the current study, experimental results on ultrasonic processing in deionised water and in liquid aluminium (Al) are reported. Cavitation activity was determined in both liquid environments using an advanced high-temperature cavitometer sensor. In water, the highest cavitation activity is obtained for the lowest sonotrode tip amplitudes. Below the sonotrode, the cavitation intensity in liquid aluminium is found to be four times higher than in water.